Joining end-to-end tubing of dissimilar materials by forming. (January 2017) - Alves, L.M.; Nielsen, C.V.; Silva, C.M.A.; Martins, P.A.F.
Abstract: This paper presents a plastic deformation process for joining two tubes made from dissimilar materials by their ends. The process consists of two elementary tube forming operations that are carried out in a single stroke; expansion to produce two adjacent counterfacing surfaces and compression beading to lock the tubes together, and has potential to replace existing solutions based on the utilization of fastened, crimped, welded, brazed or adhesive bonded joints. The investigation combines independent characterization of the materials, experimentation in a laboratory tool system and finite element modelling. Results give emphasis to the modes of deformation and failure that are used to setup the process window and demonstrate the simplicity and effectiveness of the proposed joining process for connecting carbon and stainless steel tubes by their ends. Additional results in aluminium and carbon steel tubes that were obtained by means of a two-stroke variant of the process confirm its potential for joining two tubes made from dissimilar materials with different strengths by their ends. Highlights: Plastic deformation process for joining thin-walled tubes made from dissimilar materials by their ends. Potential for replacing the utilization of fastened, crimped, welded, brazed or adhesive bonded joints. Two stroke variant of the process for joining tubes of dissimilar materials with very different strengths.